2020
DOI: 10.1088/1757-899x/876/1/012007
|View full text |Cite
|
Sign up to set email alerts
|

Design and Implementation of Interface Circuits Intended for Printed Piezoelectric Micropower Harvesters on Flexible Substrates

Abstract: Interface circuits with low power dissipation is proposed and implemented, which is useful for efficient AC/DC voltage conversion of thin-film piezoelectric micro-power stack mounted harvesters. The focus is on low-power (< 1 μW) elements consisting of printed PVDF-TrFE piezoelectric polymer on BaSrTiO3 coated flexible substrate with total thickness of the stack 3.1 μm. Using silver thin films as bottom and top electrodes, the samples exhibited stable piezoelectric rms voltage between 200 mV and 400 mV prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…In cases where a higher output voltage is required, multipliers with a larger multiplication factor are used. Figure 19 shows a circuit diagram of a voltage quadrupler [45,60,61]. Compared to the voltage-doubler circuit, the voltage-quadrupler circuit results in a lower energy efficiency value because it contains a larger number of passive components.…”
Section: Voltage Quadruplersmentioning
confidence: 99%
See 1 more Smart Citation
“…In cases where a higher output voltage is required, multipliers with a larger multiplication factor are used. Figure 19 shows a circuit diagram of a voltage quadrupler [45,60,61]. Compared to the voltage-doubler circuit, the voltage-quadrupler circuit results in a lower energy efficiency value because it contains a larger number of passive components.…”
Section: Voltage Quadruplersmentioning
confidence: 99%
“…One of the main trends in the construction of lowpower electronic converters is increasing the output power (>1 mW and mainly providing a larger output current) and simultaneously reducing the power dissipation (≤10 µW). As can be seen in Tables 1 and 2, a higher value for electrical energy efficiency can be achieved by designing the electronic circuits basically using circuit variants of synchronized switch harvesting on inductor (SSHI) [8,[81][82][83][86][87][88][89][90][91][92][93][94], voltage rectifiers employing MOS transistors [53,81,85,87,94] or voltage multipliers with Schottky diodes [7,[59][60][61]84,86], active diodes [82,87,91,93], cold-start-up circuits [8,11,83,89], active and sleep mode of operation [8,81], self-powered circuits from the signal source, and providing a buck/boost DC-DC converter mode of operation [92], as well as a charging control circuit for an energy storage element. An interesting implementation of an electronic circuit for a cold start, which can determine an increase in energy efficiency, is given in [55].…”
Section: Comparative Analysis Of Vibrational Energy Harvesting Systemsmentioning
confidence: 99%
“…where R 1 is the serial resistance of L 1 , L 1 is the parallel equivalent inductance and C 1 is the parallel equivalent capacitance. Based on the analysis of Equation (11) and the formulas, the basic parameters for the elements in the equivalent circuit and for the coefficients of the analytical expression of the complex resistance were obtained: k = R 1 = 200 Ω; ξ ≈ 0.01 (or Z max ≈ 850 kΩ); T 2 = 1 2π f p = 27.067 µs;…”
Section: Devices With Compositional Oxide/polymer Ferroelectric Coatingsmentioning
confidence: 99%
“…In our previous study, we found that printed PVDF-TrFE on BaSrTiO 3 (BST) sputtered film exhibited an excellent performance, and that a composition between them arose due to diffusion of the PVDF-TrFE particles between the crystallites of the BST [11]. This combination was explored for energy harvesting and energy storage applications [12].…”
Section: Introductionmentioning
confidence: 99%